A Novel Electroanalytical Biosensor Based on ZIF‐8/Acetylcholinesterase Bio‐nanohybrids for Early Management of Hirschsprung Disease. Issue 2 (15th July 2022) - Roy, Souradeep; Mathur, Ashish; Bihari Pati, Akash
Abstract: Hirschsprung's disease (HD) is characterised by missing nerve cells in the colon of infants and children which results in strained bowel movement. Under such situations, undiagnosed and untreated cases often lead to a cascade of gastrointestinal infections eventually resulting in Hirschsprung‐assisted enterocolitis which has significantly high mortality rate. This is further exacerbated by the absence of suitable, sensitive and efficient technologies to detect the pathological segment of the intestine, which could significantly reduce surgery duration in the operation theatre, as well as associated risks to patients. It therefore becomes a matter of extreme importance to develop a point‐of‐care platform for early and efficient management/identification of the occurrence of HD in neonates and older children during its onset, before it proves fatal with life‐threatening outcomes. The present work reports an electrochemical enzymatic biosensor using Zeolitic Imidazolate Framework‐8 (ZIF‐8) modified with acetylcholinesterase enzyme (AchE), for detection of HD as a function of the key biomarker – acetylcholine. The developed sensor was initially characterized using Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS), while the analytical performance and insights onto interfacial redox kinetics were assessed using Differential Pulse Voltammetry (DPV) and EIS respectively. The sensor exhibited limit of detection and sensitivity of 0.19 μM and sensitivity of 0.42 μA/μM/mm 2 with a shelf life of 1 month, while remaining unperturbed in the presence of common interferants. The performance of developed sensor was also examined in spiked serum samples and was observed to yield a high degree of linearity. Abstract :